Metal–Organic Framework Based Microcapsules. Issue 32 (15th July 2018) - He, Ting; Xu, Xiaobin; Ni, Bing; Lin, Haifeng; Li, Chaozhong; Hu, Wenping; Wang, Xun
Abstract: MOFs are a type of ideal crystalline material with rigid reticular structures whereas microcapsules are usually prepared from soft mater, such as polymers or supramolecules. The synthesis of MOF‐based microcapsules with novel nanostructures at the molecular scale remains a great challenge. Herein, we develop a competitive coordination strategy to synthesize MOF‐based microcapsules with novel bowl‐like structures. During the competitive coordination process, the infinite structures of MOFs are partially broken by the competitive reagents, thus flexibility is introduced into the rigid skeletons and results in the formation of bowl‐like microcapsules. Owing to the unique structure and composition of these nano‐structures, the microcapsules exhibit excellent performance and stability in adsorbing and removing iodine for both vapor and solution. This work describes new opportunities in designing MOF‐based microcapsules with novel structures. Abstract : MOF bowls : A competitive coordination strategy allows MOF‐based microcapsules with novel bowl‐like structures to be synthesized. Owing to the unique structure and composition of these nano‐structures, the microcapsules exhibit excellent performance and stability in adsorbing and removing iodine for both vapor and solution.